Penerapan Teori Conditio sine Qua Non Dalam PeristiwaTumpahan Minyak Di Teluk Balikpapan - Mawaddaturrokhmah; Muhamad Muhdar; Rini Apriyani (Fakultas Hukum Universitas Mulawarman, 2020)
The theory of conditio sine qua non is known in criminal law and is important in uncovering the causal relationship in criminal acts. However, it will generate problems when applied in environmental cases such as environmental pollution caused by oil pollution in Balikpapan. This study adopts a doctrinal approach including examining the Decision of the Balikpapan District Court Number: 749/Pid.B/LH/2018/PN.BPP. The theory of conditio sine qua non is not purely applied as a process of determining accountability. This theory is only applied at the investigation stage but not at the court process although in the facts of the trial there are several factors causing the oil spill in Balikpapan Bay including those who contributed in the occurrence of this case. Keywords: causality, conditio sine qua non; pollution; oil spill; environment